Correlation between orthostatic intolerance in children and levels of ACE2-Ang(1-7)-Mas axis and vitamin D - Xiao, Yao; Wu, Jinzhi; Wang, Jin; He, Tingting; Dong, Xiangyu (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the correlation between orthostatic intolerance in children and levels of the ACE2-Ang(1-7)-Mas axis and vitamin D.MethodsBlood samples were collected from 84 children with orthostatic intolerance and 307 healthy controls. After matching for age and sex, 84 children from each group were studied. The orthostatic intolerance group was divided into vasovagal syncope (n = 51) and postural orthostatic tachycardia syndrome (n = 33). Fasting blood samples were analyzed for 25(OH)D, ACE2, Ang(1-7), and hydroxylases using ELISA.Results(1) The orthostatic intolerance group had significantly lower levels of ACE2, Ang(1-7), 25(OH)D, and hydroxylases compared to controls (P < 0.05). (2) No sex differences in biomarker levels were found in the orthostatic intolerance group (P > 0.05), but boys in the control group had higher 25(OH)D levels (P < 0.001). (3) No significant differences between the two intolerance subgroups (p > 0.05). (4) Logistic regression showed lower levels of 25(OH)D, 25-hydroxylase, and Ang(1-7) correlated with higher orthostatic intolerance incidence. (5) Ang(1-7) levels of 19.39 ng/ml provided 86.9% sensitivity and 61.9% specificity for diagnosis.ConclusionReduced levels of Ang(1-7)/ACE2, 25(OH)D, and 25-hydroxylase are linked to orthostatic intolerance in children, highlighting vitamin D deficiency's role and suggesting Ang(1-7) and ACE2 as potential biomarkers. Sex does not significantly affect these biomarker levels.